2016
DOI: 10.1016/j.compbiomed.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Pain buddy: A novel use of m-health in the management of children's cancer pain

Abstract: Background Over 12,000 children are diagnosed with cancer every year in the United States. In addition to symptoms associated with their disease, children undergoing chemotherapy frequently experience significant pain, which is unfortunately often undertreated. The field of m-Health offers an innovative avenue for pain assessment and intervention in the home setting. The current study describes the development and initial evaluation of a tablet-based program, Pain Buddy, aimed to enhance pain management and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
158
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(168 citation statements)
references
References 52 publications
2
158
0
8
Order By: Relevance
“…Some studies suggested that remote monitoring of symptoms empowered patients to participate in their care and better manage their condition due to increased knowledge of their condition and symptom management strategies provided by the mobile interventions [31,[34][35][36]48]. In qualitative interviews with 11 lung and colorectal cancer patients, patients explained that this type of intervention had increased their understanding of their symptom-related problems and consequently, their confidence in their abilities to manage symptoms [36].…”
Section: Patient Empowermentmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies suggested that remote monitoring of symptoms empowered patients to participate in their care and better manage their condition due to increased knowledge of their condition and symptom management strategies provided by the mobile interventions [31,[34][35][36]48]. In qualitative interviews with 11 lung and colorectal cancer patients, patients explained that this type of intervention had increased their understanding of their symptom-related problems and consequently, their confidence in their abilities to manage symptoms [36].…”
Section: Patient Empowermentmentioning
confidence: 99%
“…Fortier et al, 2016 [34] Patients were highly satisfied with the app and perceived it to be useful. Pain and appetite disturbances were the most frequently reported symptoms.…”
Section: Mediummentioning
confidence: 99%
See 2 more Smart Citations
“…The third article deals with sedation during painful procedures and resulting in decreased suffering during procedures, less physical restraint and amnesia reporting during procedures [10]. The distraction of the child was approached in four articles, the technologies were a therapeutic toy [8], virtual reality [13], drawing on distraction techniques [11] and a tablet program [14]. Three of the technologies were tested during painful procedures.…”
Section: Assistive Technology For the Promotion Of Cancer Pain Reliefmentioning
confidence: 99%